Sleep, Pain, and Neurodegeneration: A Mendelian Randomization Study - Grover, Sandeep; Sharma, Manu, International Age-related Macular Degeneration Genomics Consortium (IAMDGC) (Frontiers in Neurology, 2022)
Our aim was to determine whether the genetic liability to sleep and pain-related traits have a causal effect on the risk of neurodegeneration in individuals of predominantly European ancestry. We selected five neurodegenerative disorders, namely Age-related macular degeneration (AMD), Alzheimer's disease (AD), Amyotrophic lateral sclerosis (ALS), Multiple sclerosis (MS), and Parkinson's disease (PD). The self-reported chronotype (CHR), morning person (MP), insomnia symptoms (INS), sleep duration (SP), short sleep (SS), long sleep (LS), and multisite chronic pain (MCP) were considered as exposures. We employed Mendelian randomization using an inverse-variance weighted (IVW) to compute the causal effect estimates using the latest available GWAS datasets. The MP phenotype was observed as the strongest risk factor for genetic liability to AMD (ORIVW=1.19, 95% CI 1.08, 1.32, P=0.00073). We observed suggestive evidence of risky effects of CHR on AMD (P = 0.0034), SS on AD (P=0.0044), and INS on ALS (P=0.0123). However, we failed to observe any role of pain. Results were robust to sensitivity analyses. Our study highlighted the role of MP as a risk factor for AMD.